Dengue virus infection of the Aedes aegypti salivary gland and chemosensory apparatus induces genes that modulate infection and blood-feeding behavior. - Shuzhen Sim; José L Ramirez; George Dimopoulos (PLoS Pathogens, 2012)
The female Aedes aegypti salivary gland plays a pivotal role in bloodmeal acquisition and reproduction, and thereby dengue virus (DENV) transmission. It produces numerous immune factors, as well as immune-modulatory, vasodilatory, and anti-coagulant molecules that facilitate blood-feeding. To assess the impact of DENV infection on salivary gland physiology and function, we performed a comparative genome-wide microarray analysis of the naïve and DENV infection-responsive A. aegypti salivary gland transcriptomes. DENV infection resulted in the regulation of 147 transcripts that represented a variety of functional classes, including several that are essential for virus transmission, such as immunity, blood-feeding, and host-seeking. RNAi-mediated gene silencing of three DENV infection-responsive genes--a cathepsin B, a putative cystatin, and a hypothetical ankyrin repeat-containing protein--significantly modulated DENV replication in the salivary gland. Furthermore, silencing of two DENV infection-responsive odorant-binding protein genes (OBPs) resulted in an overall compromise in blood acquisition from a single host by increasing the time for initiation of probing and the probing time before a successful bloodmeal. We also show that DENV established an extensive infection in the mosquito's main olfactory organs, the antennae, which resulted in changes of the transcript abundance of key host-seeking genes. DENV infection, however, did not significantly impact probing initiation or probing times in our laboratory infection system. Here we show for the first time that the mosquito salivary gland mounts responses to suppress DENV which, in turn, modulates the expression of chemosensory-related genes that regulate feeding behavior. These reciprocal interactions may have the potential to affect DENV transmission between humans.